Pretreatment of seeds with plant regulators attenuates salt stress in pumpkin: effects on germination and initial seedling development - Silva Guirra, Keylan (Revista Ciência Agronômica, 2021)
Pretreatment of seeds results in faster emergence of seedlings and uniform stand, especially under stress. Thus, the objective was to evaluate the action of plant regulators as stress attenuators during germination and initial development of pumpkin seedlings, cv. ‘Baiana Tropical’, irrigated with saline water. For this, a completely randomized design was established, in a 4 x 3 factorial scheme, with four replications. Treatments consisted of four types of water (W1 - 100% supply water; W2 - 100% fi sh farming effl uent; W3 - 100% artesian well water; W4 - mixture of 50% fi sh farming effl uent + 50% artesian well water) and three seed treatments (control, salicylic acid and gibberellic acid). The variables measured were germination, first germination count, shoot and root length, shoot and root dry mass, total soluble sugars, total amino acids and proline. The data were subjected to analysis of variance and Scott-Knott test. Pumpkin seedlings performed osmotic adjustment under saline conditions of W4 water. In addition, the treatment of pumpkin seeds with plant regulators (gibberellic and salicylic acids) favors the germination and initial development of seedlings under conditions of salt stress.